Protocol for identifying sound-activated neurons in the inferior colliculus by cFos immunostaining - Beatriz Maio; Nagore Elu; Cristina Martinez-Gonzalez; Emily K. Osterweil; Susana R. Louros (STAR Protocols)
Summary: cfos is an immediate early gene commonly used to identify neuronal activation. After loud sound stimulation, neurons in the inferior colliculus are activated and cFos is expressed in the nucleus. Here, we present a protocol for quantifying neuronal activity in response to auditory stimulation using cFos immunostaining in the mouse inferior colliculus. We then detail procedures for image acquisition and analysis.For complete details on the use and execution of this protocol, please refer to Louros et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.